Optimization of Co-pyrolysis Process for Sustainable Distributed Power and Industrial Development in Nigeria: A Pathway Analysis - Onyekwere, Okwuchi Smith; Patrick Azodo, Adinife; David Haruna, Amani (Optimality, 2024)
This paper analyzes existing research to assess the potential of co-pyrolysis for sustainable distributed power generation in off-grid Nigerian communities. A meta-analysis review methodology was used to assess the techno-economic and environmental aspects of co-pyrolysis, focusing on its ability to simultaneously address waste management and energy insecurity, encouraging industrial development. The analysis revealed a promising opportunity to utilize readily available plastic waste and agricultural residues for syngas production. The review identifies key factors influencing energy conversion efficiency and cost-effectiveness compared to traditional waste management methods. The potential sources of revenue from syngas use were explored, and the environmental concerns such as emissions and coal disposal were addressed. Additionally, the review provides a path analysis for stakeholders by highlighting knowledge gaps and suggesting areas for further research and development. The results provide valuable insights for policymakers, engineers, and researchers to develop an optimal, sustainable, cost-effective solution for off-grid electrification in Nigeria and encourage industrialization at various scales.